2004
DOI: 10.1056/nejmoa032646
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Concurrent Radiotherapy and Chemotherapy for High-Risk Squamous-Cell Carcinoma of the Head and Neck

Abstract: Among high-risk patients with resected head and neck cancer, concurrent postoperative chemotherapy and radiotherapy significantly improve the rates of local and regional control and disease-free survival. However, the combined treatment is associated with a substantial increase in adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
2,115
19
61

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,814 publications
(2,341 citation statements)
references
References 18 publications
72
2,115
19
61
Order By: Relevance
“…1,3 Another trial conducted in parallel by the US Radiation Therapy Oncology Group (RTOG) supported the role of CERT for high-risk margins, which, however, was defined as tumor at the resected margin. 2 Note that, in addition to margin status, the EORTC trial defined high risk as extracapsular extension (ECE) of lymph node disease, clinical involvement of lymph nodes There was a strong association between the number of adverse features and local control. The 5-year local control rates for patients who had 0, 1, 2, and 3 adverse features were 100%, 96%, 83%, and 71%, respectively (P 5.004).…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Another trial conducted in parallel by the US Radiation Therapy Oncology Group (RTOG) supported the role of CERT for high-risk margins, which, however, was defined as tumor at the resected margin. 2 Note that, in addition to margin status, the EORTC trial defined high risk as extracapsular extension (ECE) of lymph node disease, clinical involvement of lymph nodes There was a strong association between the number of adverse features and local control. The 5-year local control rates for patients who had 0, 1, 2, and 3 adverse features were 100%, 96%, 83%, and 71%, respectively (P 5.004).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the result, radiotherapy or chemoradiotherapy is often added postoperatively [1,7]. However, toxicities of the adjuvant therapy are considerable, predictive factors in each patient should be identified and taken to evaluate risk and benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of poor survival is related to locoregional recurrence. Adjuvant radiotherapy with or without chemotherapy has been used to improve the outcome in ''high risk'' squamous cell carcinoma of the head and neck [1,7]. The frequently identified high-risk pathologic features are close or positive surgical margins and extracapsular nodal extension which are usually not found in early-stage OTC [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the gross tumor volume is statistically significantly larger with 18F-FDG PET/CT–based assessment than with CT-based assessment 5152. There is still a high risk of locoregional recurrence (18%-31%) and distant metastasis (20%-25%) despite aggressive treatment 5354. The sensitivity, specificity and accuracy of 18 F-FDG PET/CT in restaging patients with head and neck cancer are 88%, 78% and 86%, respectively 55…”
Section: Methodsmentioning
confidence: 99%